New Face of Neuroinfection; Autoimun Encephalitis - Andika Okparasta (HM Publisher, 2017)
Encephalitis is an inflammatory process of the brain that attacks the central nervous system and can cause neurological dysfunction. Encephalitis is mostly caused by viruses, but in some cases the etiology is unknown. Autoimmune encephalitis occurs due to autoantibody interactions characterized by symptoms of central nervous system disorders. Clinical symptoms are quite specific, but there are criteria that must be met to make a diagnosis and additional investigations if needed. Treatment options for autoimmune encephalitis range from agents that suppress the immune system broadly to agents that specifically target antibody-mediated pathogenesis.